Nurturing Numeracy Literacy Via Online Learning: A Case Study on the Effectiveness of the Online Forum Discussion - Raziana Che Aziz; Chiam Chooi Chea; Zulaihan Ismail (2021)
Numeracy skills is one of the required skills in the Malaysian Qualification Framework (MQF) for tertiary education in Malaysia. Numeracy skills is recognised as one of the must-have daily skills because it develops logical thinking and reasoning strategies in one’s daily activities. Numeracy skills is a quantitative skill and living skill needed to solve problems and make sense of numbers, time, patterns, and shapes for daily activities. Having an adequate level of numeracy can improve many aspects of our life, including social life, education, and employment opportunities. Nevertheless, numeracy courses are also one of the most difficult courses and hence, it is vital to instill this skill for graduates. It will pose a greater challenge to adult learners in the open distance learning (ODL) environment. This study is carried out to explore the effectiveness of online forum discussion for Numeracy topic in Learning Skills for 21st century course (OUMH1603) using three essential elements in the online learning process – teaching presence, social presence, and cognitive presence. The outcome of this study will be useful to facilitate effective and quality teaching and learning processes for this topic. (Abstract by authors)